2005
DOI: 10.1007/s00213-004-2066-5
|View full text |Cite
|
Sign up to set email alerts
|

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine

Abstract: The current data do not provide evidence that repeated exposure to ketamine, albeit limited, is associated with sensitization to the behavioral effects of ketamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…In our longer-term follow-up data, we found no evidence of ketamine abuse by subjects following study participation and no evidence of subsequent psychiatric problems related to ketamine exposure (alone or in combination with other study drugs). A recent analysis of this data failed to find evidence of sensitization to the effects of ketamine in those subjects who had more than one exposure to this drug (Cho et al 2005). These findings are consistent with the lack of long-term effects reported with anesthetic doses of ketamine (Corssen et al 1971;Moretti et al 1984) and further document the safety of subanesthetic doses of ketamine as a psychopharmacologic probe in healthy subjects.…”
Section: Discussionsupporting
confidence: 78%
“…In our longer-term follow-up data, we found no evidence of ketamine abuse by subjects following study participation and no evidence of subsequent psychiatric problems related to ketamine exposure (alone or in combination with other study drugs). A recent analysis of this data failed to find evidence of sensitization to the effects of ketamine in those subjects who had more than one exposure to this drug (Cho et al 2005). These findings are consistent with the lack of long-term effects reported with anesthetic doses of ketamine (Corssen et al 1971;Moretti et al 1984) and further document the safety of subanesthetic doses of ketamine as a psychopharmacologic probe in healthy subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, a placebocontrolled, randomized, double-blind psychopharmacological trial found that intravenous ketamine (0.23 and 0.5 mg/kg) impaired performance on tasks that tested executive function in humans [45]. There is no evidence that repeated ketamine exposure increases psychotic, perceptual, euphoric, or anxiogenic responses [46]. Ketamine administration at sub-anesthetic doses has been consistently shown to present an acceptable level of risk in healthy individuals throughout their participation in a study [47].…”
Section: Cognitive Effects Of Ketaminementioning
confidence: 99%
“…Subjects were informed about the potential for psychosis, anxiety, and panic. Individuals at risk for psychosis were excluded from participating in these studies after undergoing a rigorous screening process described elsewhere (e.g., Krystal et al 2005a,b;Cho et al 2005). Subjects received ketamine hydrochloride or placebo (Ketalar, Parke-Davis, Kalamazoo, MI, USA) by intravenous route in a randomized, counterbalanced order under double-blind, placebo-controlled conditions.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Many factors may play a role in determining the response to ketamine, some of which have only recently begun to be investigated, including family history of alcohol abuse (Petrakis et al 2004), previous exposure to ketamine (Cho et al 2005), and genetic variation in the apolipoprotein E epsilon 4 allele . Other important factors have not been investigated adequately so far due to small sample sizes.…”
Section: Introductionmentioning
confidence: 99%